Graphs and Algorithms celebrating a fifty-year landmark - de Figueiredo, Celina M. H.; Protti, Fábio; dos Santos, Vinicius F. (Journal of the Brazilian Computer Society, 2026)
Landmarks are important and yet hard to celebrate. We have the privilege of witnessing Jayme Luiz Szwarcfiter reach 48 supervised doctoral theses as we celebrate the 50th anniversary of his own doctoral degree. The past five decades have witnessed the birth and growth of a vibrant research community on Graphs and Algorithms in Brazil, covering both the diversity of themes and the diversity of regions of our continental country. Jayme has acted as a key catalyst in articulating collaborations beyond the regions of Brazil to reach Argentina, Mexico, and Chile. He has fostered regional and international collaboration and helped consolidate different research groups in Latin America. On this landmark occasion, we describe some of the noteworthy achievements of our community, with special attention to Professor Szwarcfiter’s role.